Socio-demographic predictors of perceived burden of care among care givers of non-mentally and mentally retarded students in Ibadan, Nigeria (2019)
The care of mentally retarded children is often stressful experiences for family members, as the child grows up and disability becomes quite noticeable by others, parents face a very distressing predicament of social embarrassment and stigma, they require more attention and time while at the same time the need for special equipment, and medical care increases; implicating financial income and capability of the care providers. The aftermath effect on the care provider(s) most often is restrictive and disruptive to economic, social or emotional deficiency. The study examines the influence of socio-demographic variables on care burden of care providers of non-mentally and mentally retarded students in Ibadan metropolis. The study adopted cross sectional research design across types of job, social support, religion, ethnicity and age. A total number of 100 care providers participated in the study (50 care providers of non-mentally retarded students & 50 care providers of the mentally retarded students). The instruments that were used was Care Givers Burden Scale developed by Zarit et al (1980). The result of the study revealed that demographic variables (age, sex, marital status, education level, job type, religion and ethnicity) do not jointly predict burden of care among care providers of mentally retarded students in Ibadan metropolis. [F(7,43)=1.722;p>.05], but revealed that demographic variables jointly predict burden of care among care providers of non-mentally retarded students in Ibadan metropolis. [F(7,43)=2.39;p<.05], and finally revealed that social support had significant influence on burden of care among care providers of mentally retarded students in Ibadan metropolis [t(98)= 11.13; P<.05]. The study therefore concludes that demographic variables jointly predict burden of care among care providers of non-mentally retarded students not mentally retarded students. While social support was found to significantly influence burden of care among care providers of mentally retarded students in Ibadan metropolis